2021
DOI: 10.1111/tan.14332
|View full text |Cite
|
Sign up to set email alerts
|

Allograft recognition by recipient's natural killer cells: Molecular mechanisms and role in transplant rejection

Abstract: The current transplant immunology dogma defends that allograft rejection is initiated by recipient's adaptive immune system. In this prevalent model, innate immune cells in general, and natural killer (NK) cells in particular, are merely considered as downstream effectors which participate in the destruction of the graft only upon recruitment by adaptive effectors: alloreactive T cells or donor‐specific antibodies (DSA). Challenging this vision, recent data demonstrated that recipients' NK cells are capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 84 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…The current transplant immunology dogma states that the innate immunity is not powerful enough to effectively reject an allograft on its own. However, growing evidence suggests a key role of NK cells in the pathogenesis of immune-mediated graft damage in kidney transplantation [ 76 , 77 , 78 ]. The dominating immune mechanisms associated with graft rejection are mediated by adaptive immune response elements.…”
Section: Sev In Solid Organ Transplantationmentioning
confidence: 99%
“…The current transplant immunology dogma states that the innate immunity is not powerful enough to effectively reject an allograft on its own. However, growing evidence suggests a key role of NK cells in the pathogenesis of immune-mediated graft damage in kidney transplantation [ 76 , 77 , 78 ]. The dominating immune mechanisms associated with graft rejection are mediated by adaptive immune response elements.…”
Section: Sev In Solid Organ Transplantationmentioning
confidence: 99%
“…This is followed by further secretion of cytokines and chemokines by neutrophils, in order to recruit additional immune cells, such as NK cells and monocytes, which can differentiate into macrophages and dendritic cells (DCs) [53]. Recipient NK cells are suggested to undergo priming to full effectors upon IRI, which may have long-term consequences in later vulnerability to rejection episodes [54]. Presentation of alloantigens by antigen presenting cells will induce an adaptive immune response and T cell allorecognition, leading to prolonged inflammation.…”
Section: Immune Cellsmentioning
confidence: 99%
“…This, in turn, may increase the HLA expression on the cell surface and propagate antibody-mediated damage. In addition, NK cells seem to be capable of allorecognition by sensing the absence of self HLA class I molecules [54].…”
Section: Nk Cellsmentioning
confidence: 99%
“…Natural killer (NK) cells are well known to play a decisive role as a first line of defence against pathogens and tumour cells, contributing both to innate and adaptive immunity ( 1 ). More recent studies have also suggested that NK cells make an important contribution to the rejection of organ allografts ( 2 , 3 ). The extent of intra-graft NK cell infiltrates was shown to strongly predict graft survival and even to outperform conventional histologic rejection criteria ( 4 ).…”
Section: Introductionmentioning
confidence: 99%